Fabrication and studies of LaFe2O3/Sb2O3 heterojunction for enhanced degradation of Malachite green dye under visible light irradiation - Jabeen, Sabeeha; Ganie, Adil Shafi; Ahmad, Nafees; Hijazi, Shariqah; Bala, Shashi; Bano, Daraksha; Khan, Tahmeena (Elsevier B.V., 2023)
Visible light-driven photocatalysts with less charge transfer resistance and large separation are considered promising materials to address the challenges of environmental contamination. In this study, a nanocomposite of lanthanum ferrite and antimony oxide heterojunction (LaFe2O3/Sb2O3) was synthesized by facile hydrothermal method for photocatalytic degradation of malachite green (MG) dye under the irradiation of visible light. The synthesized nanocomposite was characterized by various analytical techniques including Fourier Transform Infrared Spectroscopy (FTIR) for functional group analysis, X-ray Diffraction (XRD) for phase purity and crystallinity, Scanning electron microscopy (SEM) for surface structure analysis, and energy dispersive spectroscopy (EDS) for surface composition. Moreover, the surface areas of the prepared samples were determined by the electrochemical double-layer capacitance (EDLC) using cyclic voltammetry. Impedance studies demonstrated lower charge transfer resistance for the heterojunction as compared to lanthanum ferrite and antimony oxide. The photocatalytic activity of the samples was checked for the decolorization of malachite green. It was observed that the nanocomposite showed maximum response with 98% degradation of MG in 88 minutes. Scavenging experiments established the involvement of hydroxyl radicals (OH) in the photodegradation mechanism of malachite green, while recycling experiments demonstrated its reliability and long-term use as a photocatalyst.
This paper published with affiliation IIT (BHU), Varanasi in open access mode.
Keywords: Electrochemical double layer capacitance; Impedance; LaFe2O3/Sb2O3; Malachite green; Nanocomposite; Photocatalyst